ChemInform Abstract: Catalytic Oxidation of β‐Keto Esters by Manganese(III)/Cobalt(II) and Consecutive Cyclization to Heterocycles. Issue 13 (March 2015) - Ju, Yeming; Miao, Di; Seo, Jeong Gil; Koo, Sangho
Abstract β‐Keto esters are catalytically oxidized by Mn(III)/Co(II)‐system to α‐oxo esters, which directly cyclize to dihydropyrans or furans.